PENGARUH KEDISIPLINAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 6 PAREPARE - Devita Sari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This research aims to determine the effect of student discipline on the mathematics learning outcomes of class VIII students at UPTD SMP Negeri 6 Parepare, while this type of research is Ex Post Facto research. The population of this study were students of class VIII UPTD SMP Negeri 6 Parepare. The sample in this study consisted of 35 students. This research data was obtained using a research instrument in the form of a disciplinary questionnaire and the average score of mathematics assignments given twice by subject teachers with material on number patterns in the odd semester of the 2023/2024 academic year. The data collection techniques used are questionnaire techniques and documentation techniques. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis of class VIII students at SMP Negeri 6 Parepare for the odd semester of the 2023/2024 academic year, there were 35 respondents who were analyzed based on their level of discipline, namely for students in the high discipline category there were 25 respondents with an average learning outcome of 81.04 in the high learning outcomes category. , for students in the moderate discipline category there were 10 respondents with an average learning outcome of 76.7 in the moderate learning outcomes category. The results of inferential analysis based on the Independent Samples T-Test showed that there was an influence of discipline on the mathematics learning outcomes of class VIII UPTD students at SMP Negeri 6 Parepare for the odd semester of the 2023/2024 academic year. The results of the analysis show that the significant value in the Independent Samples T-Test is 0.010 < α (? = 0.05), so Ho is rejected. H¬1 is accepted, which means there is an influence of the level of discipline on students' mathematics learning outcomes.